Postoperative liver dysfunction in gastric cancer patients following early enhanced nutritional protocols: a retrospective observational study - Kazuo Kobayashi; Satoshi Ida; Masanari Tsuji; Arisa Nawa; Takeshi Aoyama; Takashi Yokokawa; Yoshikazu Tateai; Shuichi Watabe; Hisanori Shimizu; Souya Nunobe; Masakazu Yamaguchi (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Postoperative liver dysfunction has been　recognized as a potential complication following gastric cancer surgery, particularly in the context of enhanced perioperative nutritional management. Although early supplementation with amino acids and fat emulsions has been introduced to optimize recovery, its impact on postoperative liver function remains insufficiently elucidated. This study aimed to evaluate the incidence, time course, and risk factors of postoperative liver dysfunction, and to assess the safety of early nutritional support in this context. Methods This retrospective observational study included patients who underwent radical gastrectomy between January and July 2020 at Cancer Institute Hospital Ariake. All patients received early postoperative nutritional support including amino acid and fat emulsion supplementation. Liver function was assessed based on serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and total bilirubin (T-Bil) levels on postoperative days (POD) 1, 3, 7, as well as at the first outpatient visit. Postoperative liver dysfunction was defined according to the Common Terminology Criteria for Adverse Events (CTCAE) version 5.0. Risk factors for liver dysfunction on POD 7 were assessed using by univariate and multivariate analyses. Results Data for 170 patients were analyzed. AST and ALT levels showed a biphasic pattern, with two distinct peaks observed on POD 1 and POD 7. The incidence rates of Grade 1 or higher elevations were 51.8% for AST and 39.4% for ALT on POD 1, and 47.9% for AST and 42.0% for ALT on POD 7. At the first outpatient visit, the incidence declined markedly. Univariate analysis identified acetaminophen use as a significant risk factor for liver dysfunction on POD 7 (p < 0.05), with open surgery and extensive procedures showing trend-level associations. Multivariate analysis confirmed acetaminophen use as an independent risk factor. Importantly, no significant association was found between liver dysfunction and the administration of amino acids or fat emulsions, suggesting that early postoperative nutritional management appears to be safe. Conclusions Postoperative liver dysfunction is not uncommon in gastric cancer patients but is generally transient and clinically manageable. Early postoperative nutritional management, including amino acid and fat emulsion supplementation, appears to be safe and does not adversely affect postoperative liver function when appropriately administered. Careful monitoring of liver function, particularly in patients receiving acetaminophen, remains essential to optimize postoperative outcomes.